2013
DOI: 10.1093/infdis/jit603
|View full text |Cite
|
Sign up to set email alerts
|

The First Identification and Retrospective Study of Severe Fever With Thrombocytopenia Syndrome in Japan

Abstract: SFTS has been endemic to Japan, and SFTSV has been circulating naturally within the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

24
594
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 745 publications
(645 citation statements)
references
References 24 publications
24
594
0
6
Order By: Relevance
“…To the authors' knowledge, there are only 2 reports in the literature of ulcerative lesions found in a patient with SFTS, including the previous study describing imaging findings of ulcerative lesions via postmortem pathological examination (3), with the present study being the first report to describe real-time imaging of ulcerative lesions with continuously oozing hemorrhage detected through GI endoscopic examination.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…To the authors' knowledge, there are only 2 reports in the literature of ulcerative lesions found in a patient with SFTS, including the previous study describing imaging findings of ulcerative lesions via postmortem pathological examination (3), with the present study being the first report to describe real-time imaging of ulcerative lesions with continuously oozing hemorrhage detected through GI endoscopic examination.…”
mentioning
confidence: 81%
“…This disease was first reported to be endemic to China in 2011 (1,2), and later reported to be endemic to Japan and South Korea (3,4). Hemorrhagic symptoms such as gingival oozing, bloody diarrhea, and hematuria are commonly observed in patients with severe and fatal SFTS (3,5,6).…”
mentioning
confidence: 99%
“…Although the majority of patients are farmers who live in wooded upland areas and work in the fields, a few clusters of cases and human-to-human transmission through direct contact with blood or respiratory secretions have also been reported (Bao et al, 2011;Gai et al, 2012). Human infection of SFTSV has been identified retrospectively in Korea and Japan (Kim et al, 2013;Takahashi et al, 2014). SFTSV and related viruses have also been isolated in ticks collected in Korea and Australia Yun et al, 2014).…”
mentioning
confidence: 99%
“…Since then, SFTS cases have been reported in many countries, like South Korea, Japan, and the US (3)(4)(5). Prior to 2013, there were as many as 10,000 SFTS cases worldwide (6).…”
Section: Introductionmentioning
confidence: 99%